Strategi Digitalisasi Penghimpunan Dana Zakat Melalui QRIS dan Efektivitasnya di Baznas Kota Medan - Siti Aisyah; Zulhendry Zulhendry; Muhammad Zuhirsyan; M. Rikwan Effendi Salam Manik; Anriza Witi Nasution (Studia Economica : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the strategy and effectiveness of digitization in collecting zakat funds through QRIS (Quick Response Code Indonesian Standard) at BAZNAS Medan City. The development of digital technology has brought significant changes in various aspects of life, including the zakat payment system. The use of QRIS by BAZNAS Medan City is an innovative step to make it easier for muzakki to pay zakat digitally, without having to come directly to the office. This study uses a qualitative approach with a descriptive method, through data collection techniques such as observation, in-depth interviews, documentation, and triangulation of six sources consisting of zakat managers, zakat collectors, and muzakki. The results of the study show that the strategy for collecting zakat funds through QRIS is carried out through digital socialization, collaboration with banking institutions, and strengthening digital zakat literacy. The effectiveness of using QRIS can be seen from the increase in the number of digital zakat transactions, ease of access for muzakki, and increased transparency and accountability of institutions. However, challenges are still found, such as a lack of public understanding of the use of QRIS and a lack of ongoing promotion. This study concludes that the use of QRIS is effective in supporting digital zakat fund collection at BAZNAS Medan City, but requires more intensive educational and promotional strategies to optimize the role of zakat digitalization.